(untitled) (Research, Society and Development, 2022)
The use of medicinal plants is a very common practice in order to prevent or control various diseases, with the elderly being the main influencers of this practice, which are transmitted orally between generations. With this, the objective of the study was to analyze the knowledge, use and perception of a group of elderly participants of the Vila Bananeiras Community Center about medicinal plants. The study is classified as experimental, with a sample size of 10 female participants. And for data collection, a visit to the community center was carried out, where it was possible to invite and explain the participants about the purpose of the research, and then carry out the interview. It is worth mentioning that only the elderly women who signed the Free and Informed Consent Form became part of the study. After data collection, it was identified that most of the elderly at the community center are aged between 60 - 69 years old, with complete elementary education and receive 1 salary per month, have chronic diseases, especially arthritis/arthrosis, osteoporosis, diabetes. and hypertension. Regarding the use of medicinal plants, 100% of the elderly women reported using, mainly boldo, lemongrass and lemon balm, the participants also reported that they never felt any unwanted effects after using medicinal plants. It is concluded that it is necessary to provide guidelines on the use of medicinal plants, since their use generates benefits, but inappropriate use can lead to problems in the lives of those who are ingesting them.